ON THE MEANING OF 'CAPITAL' - Dunham, Clive F. (The Accounting Review, 1930)
This article discusses various aspects of capital. One aspect of capital stock is that it is an aliquot share in profits and residual ownership rights; a second aspect is that it represents the amount contributed. Both aspects of capital stock could be given adequate recognition by means of par value stock, if discounts thereon and premiums were considered unobjectionable, for if these be inseparable from the par account, the three elements together would be the sum actually contributed. The difficulty is that corporation law makes it inadvisable openly to treat par value, adjusted by premiums And discounts, as the capital. The legal definition of capital is the natural outcome of the kind of problems presented in litigation. One argument showing the derivation of the lawyer's definition is as follows. Capital marks the limit of the liability of the stockholders to the creditors. The creditors cannot rely on the private assets of the stockholders. These rights and duties, according to one view of thee matter, are implied by law, as stipulations in the contract presumed to run between the corporation and the creditor at the time credit is extended.